Fenomena Underpricing: Sebelum, Saat dan Setelah Covid-19 Melanda Indonesia - Murtini, Umi (Seminar Nasional Manajemen, 2024)
This study aims to examine the effect of profitability, company size and capital structure on underpricing with industry type as a control variable. The study was conducted before, during and after Covid-19 hit Indonesia. Profitability was measured using Return on Asset (ROA). Company size was measured using natural logarithm of total assets. Capital structure was measured using debt to total assets. Industry type used a dummy variable. The test used weighted least square and mean difference test. The test results showed that ROA had a positive effect on underpricing for the entire period. Company size had a negative effect for the period before and during Covid-19. After Covid-19, company size had a positive effect. Capital structure had a negative effect on underpricing for the period before and after Covid-19, but during Covid-19, capital structure had no effect. Energy industry types affect underpricing in the pre-covid-19 period. Types of industries that were affected during covid-19 were consumer cyclicals, basic materials, and technology. After covid-19 ended, all industries affected underpricing. Underpricing value before, during and after Covid-19 was no different. It is recommended that issuers can increase funds through a stock IPO without considering whether the economic situation as long as the company's ROA is always good. The limitation of the research is the limited data for the period after Covid-19, so the results of this research may not be able to provide a true picture. Further research, it is recommended to examine investor behavior when buying IPO shares using behavioral method.